A comparison of antioxidant capacity and some lipoprotein values in swimmers and sedentary subjects - Gökhan, I.; Aktas, Y.; Arikan, G. (Journal of Human Sport & Exercise, 2014)
Increased oxygen consumption as a result of the exercise also increases the free radical production. These free radicals are neutralized by a defence mechanism consisting of enzymatic and non-enzymatic antioxidants. Training can have positive or negative effects on oxidative stress depending on the load and type of the training or the status of the individual prior to it. The purpose of this study is to search the capacity of lipoproteins, total oxidant and antioxidant in swimmers and sedentary subjects. The experimental group were 18 male children with mean age 15,16 ± 0,92 who have been swimming at least for 2 years and exercise regularly 3 days a week and 2 hours a day, as the control group, 18 male children with mean age 15,33 ±1,08 who do not regularly do any particular sports, participated voluntarily in our study. Oxidant-antioxidant measurements were conducted through venous blood samples collected in EDTA tubes on an empty stomach and at rest. Total Antioxidant Capacity (TAC) was determined through a method developed by Erel (2004) to measure the total antioxidant capacity of the body against the free radicals. Lipid Hydroperoxide (LOOH) determination was specified with a method in which xylenol orange and Fe++ are used (Arab and Steghens, 2004). Total Oxidant Status (TOS) was determined through a colorimetric method developed by Erel (2004). Oxidative Stress Index (OSI) was calculated with the formula Total Oxidative Stress (TOS) / (TAC). Plasma triglyceride, Total cholesterol, LDL, HDL, VLDL parameters were measured using Abbot and automatic chemistry analyser (Aeroset, Abbott, USA). For the comparison of the experiment and the control groups, Independent Samples T-Test was applied to compare the independent groups on the SPSS 16.00 statistical package. Statistically significant difference was determined to be p<0,05. No statistically significant difference was observed between the body composition values of the experiment and the control groups (p>0,05). Moreover, a statistically significant difference was observed between TAC, LOOH, TOS, OSI, TRIGLISERIT and HDL values of the experiment and the control groups (p<0,05; p<0,01). No statistically significant difference was observed between both groups in terms of Cholesterol, LDL and VLDL values (p>0,05). It was concluded that total antioxidant and antioxidant capacity of the swimmers` group was higher compared to the sedentary group. The reason for this difference, we think, is that antioxidant defence mechanisms of the subjects who do swimming are more developed.